The role of young people and social media in promoting fascinating Sungai Petani - Mohd Yusof, Noorlailahusna; Azizan, Intan Syahriza (Universiti Teknologi MARA, Kedah, 2024)
This article explores the ways in which young people, acting as social agents, utilise social media to promote local communities. Through the utilisation of digital platforms, these young individuals are exerting a growing impact on the economic, cultural, and social aspects of their local environments. The problem addressed is the need to understand the effectiveness of social media in reaching and engaging audiences. The objective is to evaluate the effectiveness of social media platforms used by young people in reaching a target audience. A quantitative method was employed to track the number of views, likes, shares, and comments of a promotional video over a specified 30-day timeframe. The major results indicate significant audience engagement, evidenced by high numbers of views, likes, shares, and comments. The results also emphasise the significant influence of social media initiatives driven by young people in improving local visibility and engagement. By improving the visibility of local communities, this strategy aims to increase the number of visitors to Sungai Petani and simultaneously enhance the socio-economic level of local people and the area. The conclusion highlights the potential of young people as influential social agents in promoting local communities through the use of social media.